The mechanisms of pain tolerance and pain-related anxiety in acute pain. Issue 2 (November 2019) - Cimpean, Alina; David, Daniel
This study emphasizes the role of pain catastrophizing and state anxiety on pain tolerance and pain-related anxiety. Response expectancies for pain tolerance and pain intensity were tested as potential mediators. A cold-pressor task was used on a healthy sample. Measures were taken before and after cold-pressor procedure, while aversive versus neutral information regarding the cold-pressor task was given prior to the pain induction. An exploratory path model was conducted. Similar paths for pain tolerance and for pain-related anxiety were shown in aversive condition. Also, psychological measures may explain pain experience in aversive context.